Brain imaging in classic nonketotic hyperglycinemia: Quantitative analysis and relation to phenotype. Issue 3 (20th March 2019) - Stence, Nicholas V.; Fenton, Laura Z.; Levek, Claire; Tong, Suhong; Coughlin, Curtis R.; Hennermann, Julia B.; Wortmann, Saskia B.; Van Hove, Johan L.K.
Abstract: Patients with severe nonketotic hyperglycinemia (NKH) have absent psychomotor development and intractable epilepsy, whereas attenuated patients have variable psychomotor development and absent or treatable epilepsy; differences in brain magnetic resonance imaging (MRI) between phenotypes have not been reported. In a retrospective cross‐sectional study, we reviewed 38 MRI studies from 24 molecularly proven NKH patients, and 2 transient NKH patients. Quantitative analyses included corpus callosum size, apparent diffusion coefficient, automated brain volumetric analysis, and glycine/creatine ratio by spectroscopy. All patients age <3 months had restricted diffusion in the posterior limb of the internal capsule, anterior brainstem, posterior tegmental tracts, and cerebellum, not present in transient NKH. In older infants, the pattern evolved and included generalized diffusion restriction in the supratentorial white matter, which quantitatively peaked between 3 and 12 months. No patient had absent corpus callosum or gyral malformation. The corpus callosum was relatively short in severe compared to attenuated phenotypes, and thin in severe cases only. The corpus callosum growth rate differed by severity; age‐matched Z ‐scores of thickness worsened in severe cases only. Cerebral volume was decreased in the hippocampus, globus pallidus, cerebral cortex, thalamus, and cerebellum. Severe patients had greatest glycine/creatine ratios. In this study, no brain malformations were identified. The growth failure of the corpus callosum is worse in severe NKH, whereas the diffusion restriction pattern, reflecting microspongiosis, does not discriminate by phenotypic severity. NKH is therefore a disorder of brain growth best recognized in the corpus callosum, whereas spongiosis is not prognostic.